2020
DOI: 10.1172/jci.insight.133019
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate cathepsin K secretion promotes its enzymatic activation driving heart and valve malformation

Abstract: Although congenital heart defects (CHDs) represent the most common birth defect, a comprehensive understanding of disease etiology remains unknown. This is further complicated since CHDs can occur in isolation or as a feature of another disorder. Analyzing disorders with associated CHDs provides a powerful platform to identify primary pathogenic mechanisms driving disease. Aberrant localization and expression of cathepsin proteases can perpetuate later-stage heart diseases, but their contribution toward CHDs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…A similar process was suggested to take place in medaka fish, in which RANKL (Receptor activator of NF-κB ligand) was ubiquitously overexpressed . Some caution is warranted, as ctsK also labels mesenchymal cells in some tissues (Debnath et al, 2018;Lu et al, 2020) and we observed immobile ctsk:nlsmCherry+ nuclei at a distance from the opercle, in locations unlikely to contain osteoclasts (data not shown). It is noteworthy that conversion of macrophages to osteoclasts depends on inflammatory signals such as Tnf-α .…”
Section: Discussionmentioning
confidence: 85%
“…A similar process was suggested to take place in medaka fish, in which RANKL (Receptor activator of NF-κB ligand) was ubiquitously overexpressed . Some caution is warranted, as ctsK also labels mesenchymal cells in some tissues (Debnath et al, 2018;Lu et al, 2020) and we observed immobile ctsk:nlsmCherry+ nuclei at a distance from the opercle, in locations unlikely to contain osteoclasts (data not shown). It is noteworthy that conversion of macrophages to osteoclasts depends on inflammatory signals such as Tnf-α .…”
Section: Discussionmentioning
confidence: 85%
“…10A-B). The involvement of autophagy was further investigated using the autophagy defective gnptab -/- zebrafish (Lu et al, 2020; Willet et al, 2018). No difference was detected in NaR cell reactivation between gnptab -/- fish and their siblings, indicating that autophagy does not play a major role in NaR cell reactivation (Supplemental Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The noa mutant line, dlat -/- (Taylor et al, 2004) was obtained from the Zebrafish International Resource Center (ZIRC). Mutant gnptab -/- fish were obtained from Dr. Heather Flanagan-Steet, Clemson University (Lu et al, 2020). The fish were genotyped as previously reported (Liu et al, 2020; Xin et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have successfully established zebrafish models to study LSDs, including mucolipidosis type II [45][46][47][48] . Since our data indicated that GCAF is required for the cleavage and activation of GNPT α/β precursor, we asked if their knockouts share similar developmental defects in zebrafish.…”
Section: Gcaf Deficiency Phenocopies MLII In Vivomentioning
confidence: 99%